Viscous Dissipation Effect on the Mixed Convection Boundary Layer Flow towards Solid Sphere - Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (Universiti Malaysia Sabah, 2016)
In this study, the steady mixed convection boundary layer flow and heat transfer towards solid sphere with viscous dissipation effect is considered. The non linear parabolic partial differential equations are transformed before being solved numerically by Keller-box method. The effects of different Prandtl number values, the parameter of mixed convection and Eckert number are elaborated. The presence of viscous dissipation effect reduced the Nusselt number which physically promoted a conduction heat transfer process along the sphere surface. Further, the Prandtl number gives more significant impact on reduction of thermal boundary layer compared to mixed convection parameter.